Pengaruh Pengangguran Terhadap Kemiskinan di Kabupaten Sorong - Pasaribu, Sandi H. (Universitas Serambi Mekkah, 2024)
The aim of this research is to determine the effect of unemployment on poverty in Sorong Regency. The analysis method used is a simple linear regression analysis method. The research results show that the unemployment variable has a significant effect on poverty, so it can be explained that the higher the amount of poverty, the lower the income earned by the community which results in a decrease in welfare which has an impact on increasing the number of poor people.